2018
DOI: 10.1016/j.kjms.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of MMP‐2 and MMP‐9 gene polymorphisms with the risk of hepatopulmonary syndrome in cirrhotic patients: A case‐control study

Abstract: Hepatopulmonary syndrome (HPS) increases the mortality of patients who suffered from liver cirrhosis, especially patients plagued by severe hypoxemia. Gene polymorphisms are reported to be related to the risk of HPS in cirrhotic patients. Thus, our study aims to elucidate the correlation between MMP‐2 and MMP‐9 gene polymorphisms and HPS in cirrhotic patients. A total of 152 cirrhotic patients suffering from HPS as well as another 152 cirrhotic patients without HPS were recruited. Polymerase chain reaction‐res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Many studies have reported the involvement of MMP9 in the development of lung diseases [29] . MMP9 polymorphism is identified to increase the susceptibility to respiratory diseases [30] [31] [32] [33] . Multiple SNPs of MMP9 have been discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the involvement of MMP9 in the development of lung diseases [29] . MMP9 polymorphism is identified to increase the susceptibility to respiratory diseases [30] [31] [32] [33] . Multiple SNPs of MMP9 have been discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly this MMP-2 rs 243865 SNP has been associated with central obesity and non-alcoholic fat liver disease and with increased risk of cirrhotic hepatopulmonary syndrome in Chinese patients. However the carriage of the variant TT genotype of this MMP-2 SNP decreased the risk for both hepatic complications [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…MMPs activity is regulated at gene expression level and by activation of latent pro-MMPs to active MMPs [16,17]. MMPs polymorphisms (SNPs) might modify gene expression and MMPs plasma levels, and indirectly in uence LF [27][28][29][30][31]. MMPs plasma levels are higher in HIV-infected naïve compared to HCV monoinfected patients [32][33][34], while effective antiretroviral therapy normalizes their plasma MMPs levels [32].…”
Section: Introductionmentioning
confidence: 99%